The many theories of mind: eliminativism and pluralism in context - Gough, J (Springer, 2022)
In recent philosophy of science there has been much discussion of both pluralism, which embraces scientific terms with multiple meanings, and eliminativism, which rejects such terms. Some recent work focuses on the conditions that legitimize pluralism over eliminativism – the conditions under which such terms are acceptable. Often, this is understood as a matter of encouraging effective communication – the danger of these terms is thought to be equivocation, while the advantage is thought to be the fulfilment of ‘bridging roles’ that facilitate communication between different scientists and specialisms. These theories are geared towards regulating communication between scientists qua scientists. However, this overlooks an important class of harmful equivocation that involves miscommunication between scientists and nonscientists, such as the public or policymakers. To make my case, I use the example of theory of mind, also known as ‘mindreading’ and ‘mentalizing’, and broadly defined as the capacity to attribute mental states to oneself and others. I begin by showing that ‘theory of mind’ has multiple meanings, before showing that this has resulted in harmful equivocations of a sort and in a way not accounted for by previous theories of pluralism and eliminativism.